Best Answer

-3x2 = 5 + 3x (add 3x2 to both sides)

0 = 3x2 + 5 + 3x or

3x2 + 3x + 5 = 0 (since the discriminant is less than zero, we have complex roots)

x = [-3 ± √[(32 - 4(3)(5)]]/2(3)

x = [-3 ± √(9 - 60)]/6

x = (-3 ± √-51)/6

x = (-3 ± i√51)/6

x = (-3 + i√51)/6 = -1/2 + (√51/6)i or

x = (-3 - i√51)/6 = -1/2 - (√51/6)i

Q: -3x squared equals 5 plus 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is a quadratic equation.

(x + 5)(3x + 1)

(3x + 1)(x + 5)

x = 25 / 3squared + 5

3x-5=3x+5 There is no solution.

Related questions

It is a quadratic equation.

(3x + 1)(x + 5)

(x + 5)(3x + 1)

x = 25 / 3squared + 5

If: y = 4x2-2x-1 and y = -2x2+3x+5 Then the length of the line works out as: 65/18 or 3.6111 ... recurring decimal 1

3x-5=3x+5 There is no solution.

5

what is a slope

(x - 1)(3x + 5)

Equations: 3x-2y = 1 and 3x^2 -2y^2 +5 = 0 By combining the equations into one single quadratic equation and solving it the points of contact are made at (3, 4) and (-1, -2)

3x+5=20 x=5 since 5x3+5=20

4x + 5 = 3x + 84x-3x + 5 - 5 = 3x - 3x + 8 -5x = 3